Avaliação da erodibilidade de um perfil de solo típico da área do campo de instrução de Santa Maria-RS - Fernandes, Leila Posser (2015)
The research that resulted in this master thesis was developed on a dirt road Instruction Campo de Santa Maria, RS. The main objective was to study the erodibility of the surface soil horizons A, B and C. The methodology consisted in the literature; field investigations and laboratory stage. In the latter were carried out tests of physical and chemical characterization, direct shear strength tests, cone penetrometer dynamic test, testing for indirect evaluation (breakdown, laboratory cone, infiltration rate and loss by immersion) and direct (Inderbitzen) erodibility . The results were compared with the proposed Bastos (1999) to estimate the soil erodibility unsaturated located in Porto Alegre.A road evaluated this on a probable fluvial terrace. Based on results of direct shear tests showed greater susceptibility to erosion to the horizon C. The test of dynamic cone penetrometer confirmed the results found by Pittelkow (2013) and Santos (2014) showing greater penetration resistance for the crust layer. In indirect evaluation of erodibility - by estimating the erodibility factor (KUSLE) soil horizons A, B and C, was between 0.24 and 0.40, making sure it can not separate these materials on the erodibility. The breakdown test showed increased susceptibility to erosion for the B and C horizons, regardless of the moisture condition. The results of the laboratory test cone was unsatisfactory with the results observed in the field. The MCT methodology presented a good relationship of correspondence between the results of the tests and the behavior of soils in the studied sites, primarily for the air condition to dry moisture, proving their applicability to the materials. Direct evaluation made through the tests Inderbitzen confirmed that the loss of soil generally is greater the larger the slope of the ramp and flow test. According to this assessment to the horizon samples B and C there was a tendency of higher values of erodibility in dry condition the air. It was also found lower values of erodibility of the horizon, standing from about 0 to 13.8 g / cm2 / min / Pa, for natural moisture condition and dry air, respectively. B horizon values stood at an intermediate level, for samples in natural moisture condition. The values for K for the C horizon stood at 65.8 g / cm2 / min / Pa for the natural moisture. Did not establish critical hydraulic stresses for the A and B horizons, the natural moisture condition, but for the other conditions ranged between 0.94 and 1.29 Pa for the horizon and 0.95 and 1.17 Pa for the B horizon to horizon C values were between 0.90 and 1.19 Pa. The B and C horizons were the materials most potentially erodible. The criteria had better correlation with geotechnical proposed Bastos (1999) were the erodibility coefficient obtained in Inderbitzen test and the erodibility criteria MCT methodology.